Recent Approaches for Broadening the Spectral Bandwidth in Resonant Cavity Optoelectronic Devices - Gun Wu Ju; Byung Hoon Na; Yong-Hwa Park; Young Min Song; Yong Tak Lee (Advances in Condensed Matter Physics)
Resonant cavity optoelectronic devices, such as vertical cavity surface emitting lasers (VCSELs), resonant cavity enhanced photodetectors (RCEPDs), and electroabsorption modulators (EAMs), show improved performance over their predecessors by placing the active device structure inside a resonant cavity. The effect of the optical cavity, which allows wavelength selectivity and enhancement of the optical field due to resonance, allows the devices to be made thinner and therefore faster, while simultaneously increasing the quantum efficiency at the resonant wavelengths. However, the narrow spectral bandwidth significantly reduces operating tolerances, which leads to severe problems in applications such as optical communication, imaging, and biosensing. Recently, in order to overcome such drawbacks and/or to accomplish multiple functionalities, several approaches for broadening the spectral bandwidth in resonant cavity optoelectronic devices have been extensively studied. This paper reviews the recent progress in techniques for wide spectral bandwidth that include a coupled microcavity, asymmetric tandem quantum wells, and high index contrast distributed Bragg-reflectors. This review will describe design guidelines for specific devices together with experimental considerations in practical applications.